Morphology analysis of hexavalent chromium reduction to trivalent chromium with syrup under different pH conditions - Zi-Fang Chen (Applied Water Science, 2019)
Abstract Batch experiments were designed to ascertain the morphology and valence of chromium in the reduction of hexavalent chromium with syrup under different pH conditions. Results indicated that the syrup reduced hexavalent chromium to trivalent chromium, and the existing forms of Cr were mainly Cr(OH)3, CrOOH and CrOOH–Fe. The percentage of Fe–Mn oxide-bound state was 29.28%, 29.28%, 22.22% and 20.12%, respectively, and the percentage of organic binding state was 64.71%, 66.58%, 74.74% and 73.14%, respectively, in the reaction systems at different pH (2.0, 2.5, 3.0 5.6) conditions.